RELATIONSHIP BETWEEN JOB STRESS AND FRAUD RISK ON EMPLOYEES AT THE NATIONAL EYE CENTER HOSPITAL X - Suhat, Suhat; Umami, Furi Destiana; Yogisutanti, Gurdani (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Fraud is any unlawful acts committed by individuals within an organization or institution to gain an illegal advantage of others through manipulation, falsifying truth and good behavior. On employees, pressure may cause fraud in part by problems stemming job stress from the work environment. The purpose of this study was to determine the relationship of job stress with the risk of fraud on employees. Methods: The study design used cross sectional. Samples were employees in the Administration, Finance, Purchasing, Human Resources, Information and Technology, and Procurement at the National Eye Center Hospital X as many as 37 people. The sampling technique used in this study was proportional random sampling. Data was collected by questionnaire. Analysis of data was done through two stages, namely univariate to see the frequency distribution and bivariate to see the relationship (chi square). Results: The result showed that Ho was rejected (p-value = 0.0001) meant that there was a relationship between job stress with the risk of fraud. Conclusion: The relationship between job stress with the risk of fraud suggests the hospital to do the job stress measurement and risk of fraud continuous and reduce employees stress levels through strategies such as redisigning organizational approaches and participatory decision-making.Â